A new blasthole XRF probe for mining grade control. Issue 1 (1st December 2018) - Hawke, P. J.; Bachmann, J.
Abstract : Mining grade control is often based on geochemical sampling of blast cones. Limitations of this method include a single assay result representing the entire length of the hole, the requirement of an on-site lab to meet turn-around times, bias generated by sampling of the blast cones and the risk of physical injury during sampling. A new XRF logging probe has been designed specifically for providing elemental analysis through wireline logging. This tool will provide a continuous geochemical log down the length of the blasthole, allowing composite samples to be generated for different sections of the hole, e.g. to provide more detailed grade control to support selective mining as several flitches within an open-pit bench. Once the system is calibrated, results can be delivered as soon as logging is complete. This paper presents the results of a series of bench tests demonstrating the accuracy and precision of the prototype BHXRF probe as a potential new grade control tool for different types of bulk commodity or base metal deposits.